Pitch Angle Distribution of MeV Electrons in the Magnetosphere of Jupiter. Issue 8 (23rd August 2022) - Nénon, Q.; Miller, L. P.; Kollmann, P.; Liuzzo, L.; Pinto, M.; Witasse, O.
Abstract: The magnetosphere of Jupiter harbors the most extreme fluxes of MeV electrons in the solar system and therefore provides a testbed of choice to understand the origin, transport, acceleration, and loss of energetic electrons in planetary magnetospheres. Along this objective, the Pitch Angle Distribution (PAD) of energetic electrons may reveal signatures of the dominant physical processes. Here, we analyze for the first time the PAD of MeV electrons observed by the Galileo‐Energetic Particle Detector (EPD) experiment in orbit around Jupiter from 1995 to 2003. We find that the MeV electron PADs observed by the integral channels of EPD appear relatively isotropic with a flux anisotropy lower than a factor of 3. Due to the relatively large angular apertures of the EPD telescopes, the actual anisotropy may be larger than the observed one. The fine anisotropy observed by Galileo‐EPD reveals persistent pancake distributions at the M‐shell of M = 9. Outward of this distance, at M = 15 and M = 20–60, MeV electron distributions have pancake, isotropic, and scattered beam field‐aligned distributions. The scattered beam distributions can either be evidence of outward adiabatic transport or may suggest that high‐latitude auroral acceleration can transiently supply as much trapped MeV electrons to the middle magnetosphere as the inward adiabatic transport of electrons from an outer equatorial reservoir. Key Points: The Pitch Angle Distribution of MeV electron fluxes, as observed by the Galileo instrumentation, is isotropic within a factor of 3 MeV electrons have persistent pancake shapes at L ∼ 9, and pancake, isotropic, and scattered field‐aligned distributions at L = 15–60 The field‐aligned distributions may be generated by outward adiabatic radial transport or auroral acceleration